Regulation of Bacterial Cell Division: Genetic and Phenotypic Analysis of Temperature-Sensitive, Multinucleate, Filament-Forming Mutants of Escherichia coli - Allen, Jane Smith (1974)
Three mutants of Escherichia coli K-12 which form filaments during 42 C incubation have been characterized. The mutant strains AX621, AX629, and AX655 continued to grow and to synthesize deoxyribonucleic acid at 42 C for 150 to 180 min, after which time growth ceased. When cultures of the mutants were transferred from 42 to 28 C, septation of the filaments began after a 25- to 30-min period and continued at a greater than normal rate until no filaments remained. Addition of chloramphenicol at the time of transfer from 42 to 28 C prevented cell division in strain AX655 and caused lysis of strains AX621 and AX629. The temperature sensitivity mutation in each strain mapped near leu. For strain AX621, the mutation was specifically located between leu and nadC by P1 transduction. Properties of these strains are compared with those of other cell division mutants.